2009 47th Annual Allerton Conference on Communication, Control, and Computing (Allerton) 2009
DOI: 10.1109/allerton.2009.5394485
|View full text |Cite
|
Sign up to set email alerts
|

Cost sharing with network coding in two-way relay networks

Abstract: Abstract-We consider a scenario in which two sources exchange stochastically varying traffic with the aid of a bidirectional relay that may perform network coding over the incoming packets. Each relay use incurs a unit cost, e.g., transmission energy. This cost is shared between the sources when packets from both are transmitted via network coding; if traffic from a single source is sent, the cost is passed on to only that source. We study transmission policies which trade-off the average cost with the average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…This work is in line with a variety of other recent papers that use game-theoretic methods to analyze network coding problems-treating either individual unicasts or individual nodes in the network as selfish decision makers [6], [10], [16], [23], [26], [28]. Most of these results are only applicable in restricted settings.…”
supporting
confidence: 78%
“…This work is in line with a variety of other recent papers that use game-theoretic methods to analyze network coding problems-treating either individual unicasts or individual nodes in the network as selfish decision makers [6], [10], [16], [23], [26], [28]. Most of these results are only applicable in restricted settings.…”
supporting
confidence: 78%
“…Some of these consider games played between unicast flows (sessions) [22], [23], [24]; thus the model and concerns in these are quite from from our game model that assumes and utilizes the multicast nature of the traffic. Among prior work, [25], [26] are closest to ours, and also consider multicast traffic.…”
Section: Related Workmentioning
confidence: 99%
“…In [7], it is observed that only one bit of queue information of the other source leads to significant improvement compared with no information for energy minimization in a bidirectional relay network where the relay applies network coding. This approach can be classified as reducing the bit-complexity [18] of message passing.…”
Section: Related Workmentioning
confidence: 99%